Anal swab findings in an infant with COVID‐19. Issue 1 (17th March 2020) - Fan, Qihong; Pan, Yan; Wu, Qingcui; Liu, Shan; Song, Xu; Xie, Zhongguo; Liu, Yang; Zhao, Liang; Wang, Zhonghong; Zhang, Yifei; Wu, Zuchuang; Guan, Lei; et al.
Abstract: Introduction: The transmission pathways of coronavirus disease 2019 (COVID‐19) remain not completely clear. In this case study the test for the novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in pharyngeal swab and anal swab were compared. Case presentation: A 3‐month‐old girl was admitted to our hospital with COVID‐19. Her parents had both been diagnosed with COVID‐19. The results of pharyngeal swab and anal swab of the little girl were recorded and compared during the course of the disease. The oropharyngeal specimen showed negative result for SARS‐CoV‐2 on the 14th day after onset of the illness. However, the anal swab was still positive for SARS‐CoV‐2 on the 28th day after the onset of the illness. Conclusion: The possibility of fecal‐oral transmission of COVID‐19 should be assessed. Personal hygiene during home quarantine merits considerable attention.